A Laguncularia racemosa (Combretaceae) and associated ground bacteria half a century after chronic oil pollution: Laguncularia racemosa (Combretaceae) and associated ground bacteria half a century after chronic oil pollution - José Guadalupe, López-Jiménez (2019)
The oil industry has generated chronic spills and its accumulation in the mangrove forest located on the southeast coast of Mexico. The evaluation of the impact of oil on the soil-root interaction of Languncularia racemosa (Lr) is basic to determine the changes in microbial activity and its biotechnological potential for land remediation. Lr is a tree that grows in these areas contaminated with weathered oil. The objective of this study was to evaluate the spatial distribution in soil of total petroleum hydrocarbons (TPH), the population of plant growth promoting bacteria, microbial respiration in the rhizoplane (RI), rhizosphere (RZ) and non-rhizospheric soil. (SNR) of Lr. For this study, an area of ​​8,000 m2 of a Histosol affected by chronic oil spill and drilling mud from the La Venta 248 oil well was used. Fifteen Lr trees were selected and samples were taken from the RI (secondary roots), from the RZ (secondary and tertiary roots with adhered soil) and SNR (organic matter). The results show differences in the amount of HTP accumulated in the organic soil. The spatial distribution of the HTP defined four study floor (S): S1: 1797, S2: 3294, S3: 5249, and S4: 10389 mg kg-1. The PHT were higher in RI of S1 and 2, but in RZ and SNR in S2 and 3. In RI of Soil 4 the population of N-fixing and P-solubilizing bacteria were stimulated in greater quantity, but Azotobacter was inhibited and Azospirillum. For the RZ of Lr Azospirillum it was favored but in the soil 2 and 4. The microbial respiration at 7, 14, 21, 42 and 63 days was stimulated by the IR followed by the RZ in the four evaluated soils, however the respiration microbial was negatively affected by oil in the RI, RZ and SNR. The results suggest that Lr is sustainable in soils with hydrocarbon contamination, and is a biostimulator of microbial activity that can be used for the natural attenuation of hydrocarbons, with a high population of N-fixing bacteria and solubilizers of P in RI with 10389 mg kg-1 of HTP derived from weathered petroleum. However, soils containing HTP higher than 4158 mg kg-1 in RI, RZ and SNR require previous treatment to remove the oil and put it in contact with the RZ of the white mangrove.